Validity of t–J approximation for extended Hubbard model with strong repulsion - Cheranovskii, V.O.; Klein, D.J.; Ezerskaya, E.V.; Tokarev, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
It is shown that for finite cyclic systems described by two band Hubbard Hamiltonian with strong electron repulsion the reduction to effective t–J model may give incorrect description of the ground state symmetry due to neglect of the correlated hopping terms.